Cultural norms and the marketplace: favor economies in the Arab world - El Jurdi, Hounaida (2020)
Purpose Recent scholarship has highlighted the complexity of buyer-seller relationships in emerging markets and called for a better understanding of the cultural norms shaping such relationships. This paper aims to draw on social capital theory to explore the role of networks and relational norms, such as wasta, in Arab culture on consumer relational behaviors. The Arab market constitutes a significant economy and social networks and relational norms are of significant value in Arab culture. Design/methodology/approach A qualitative approach was used to address the research questions. In-depth semi-structured interviews were conducted with 19 male and female consumers across Lebanon over a four-month period. Findings Social networks are heavily used in relational behaviors to achieve four types of goals, namely, self-serving goals, unity goals and equality goals and relationship maintenance goals. In fulfilling these goals consumers create economies of favors that aim at the using and maintenance of communal bonds. Research limitations/implications This study was conducted in one geographical context. While Lebanon shares many of its characteristics with other Arab countries, future research should aim at exploring the influence of social networks in other Arab and emerging market contexts. Practical implications Consumers have different motivations between formal and informal markets. The research suggests that small sellers in highly embedded markets need to use their social networks and to make their stories authentic and known within their communities to facilitate emotional connections with consumers. Originality/value Emerging markets offer opportunities to extend our understanding of marketing theory and practice. This research provides a richer understanding of Arab consumers and suggests that wasta relationships play a role in consumptive decisions and not just in business negotiations. Wasta, as a cultural form of cultural capital, is heavily used in consumption as a coping mechanism to overcome market inefficiencies.